Association of Total Zinc Intake with Myopia in U.S. Children and Adolescents. Issue 9 (September 2019) - Burke, Niamh; Butler, John S.; Flitcroft, Ian; McCartney, Daniel; Loughman, James
Abstract : SIGNIFICANCE: This present study advances our knowledge on the role of lifestyle factors in myopia (short-sightedness), specifically dietary factors. It has been suggested in previous studies that lower zinc status is associated with myopia; however, this article shows no relationship between dietary zinc intake and myopia in U.S. adolescents. PURPOSE: It has been suggested that low zinc levels may contribute to the development of myopia. The aim of the present study is to examine, for the first time in a Western population, the association of total dietary and supplement zinc intake with myopia. METHODS: A total of 1095 children/adolescents aged 12 to 19 years who participated in the U.S. National Health and Nutrition Examination Survey from 2007 to 2008 were enrolled in this study. Multivariate logistic regression analysis was performed to examine the relationship between total zinc intake and myopia after adjustment for potential confounders. In addition, the association between total zinc intake and spherical equivalent refractive error was examined in the myopia group through multiple linear regression. RESULTS: Among study participants, 30% were found to be myopic (⩽−1.00 D). Although median total daily zinc intake was lower among myopes (10.8 [10.2] mg/d) than among nonmyopes (11.1 [10.8] mg/d), the difference was not statistically significant ( P = .11). In multiple logistic regression analyses, zinc and copper intakes were not significantly associated with myopia after adjustment for age, sex, body mass index, ethnicity, family income, recreational activity, copper intake, and daily energy intake (in kilocalories per day). In multiple linear regression, spherical equivalent refractive error was not associated with total zinc intake in the myopic group after adjustment for confounding factors ( P = .13). CONCLUSIONS: In contrast to previous Asian studies, total zinc intake is not associated with the presence of myopia in U.S. adolescents/children.